Balancing risk versus benefit: the elderly patient's perspective on warfarin therapy. - Bajorek BV; Ogle SJ; Duguid MJ; Shenfield GM; Krass I (Centro de Investigaciones y Publicaciones Farmaceuticas, 2009)
Warfarin therapy is underused in the target at-risk elderly population. Clinicians perceive that older patients are reluctant to use this therapy, however the perspective of patients or their carers has yet to be explored. Objective: To explore in-depth the perspectives of elderly patients and/or their carers regarding the use of warfarin therapy. Method: A qualitative study, using semi-structured group interviews was undertaken. The audio-taped discussions were transcribed verbatim, then thematically analysed to identify emergent themes. Group discussions were conducted at a major Sydney teaching hospital, over a 2-month period. Individuals aged 65 years or older (and/or their carers) who were using long-term (6 months) warfarin therapy were recruited by voluntary response to study flyers.Results: 17 patients and carers (mean age 77.2 SD=7.5 years) participated in one of two focus groups. Five core themes emerged regarding warfarin therapy: inadequate knowledge and understanding about it, patients/carers variable experience of information provision, cycle of reactions to being on it, issues in its practical management, and the spectrum of experiences with it. Overall, participants were very accepting of the therapy, describing a high level of compliance, despite initial fears and anxieties, and a relative lack of knowledge. Patients felt somewhat abandoned in their management of warfarin due to the lack of ongoing support services in the community, and inadequate information provision.Conclusions: Elderly patients and their carers appear to be quite accepting of warfarin therapy, in contrast to the perceptions of health care professionals. More effort is needed, however, in terms of information provision, particularly in the form of community-based services, to assist patients in the long-term management of warfarin.